Machining of hard and brittle materials: A comprehensive review. (2022) - Sharma, Ankit; Kalsia, Mohit; Uppal, Amrinder Singh; Babbar, Atul; Dhawan, Vikas
Abstract: Modern machining trends are continuously expanding nowadays, especially the various vibrational-based machining processes (VBM) exemplify as ultrasonic machining, ultrasonic vibration assistant machining, and rotary ultrasonic machining (RUM) processes. Therefore, this review study has been focused on these three machining techniques with an explanation of their parameters, physics, mechanism, and application. Also reported that the rotary ultrasonic machining and other vibration-assisted machining processes are used explicitly to machine hard, and brittle material exemplifies as ceramic, glass, bone, titanium alloy, silicon carbide, etc. There is a critical need for developing the models of process performances such as cutting force, tool wear rate, surface roughness, material removal rate, etc. Therefore, improvement in the USM, rotary ultrasonic machining, and UVA technique should be considered and explore the work up to an optimum machining limit.